Low expression of estrogen receptor β in renal tubular epithelial cells may cause hyperuricemia in premenopausal patients with systemic lupus erythematosus. (April 2021) - Liu, Haijun; Peng, Liqin; Ma, Jianda; He, Liping; Long, Kangxia; Ouyang, Xia; Wu, Cuiyi; Xie, Minyan; Dai, Lie; Cai, Xiaoyan
We investigated the impact of estrogen receptor (ER) expression in renal tubular epithelial cells on serum uric acid (UA) levels in premenopausal patients with systemic lupus erythematosus (SLE). Thirty patients underwent renal biopsy: 18 with SLE (LN group) and 12 with IgA nephritis (IgAN group). ERs (ERα and ERβ) in renal tubular epithelial cells were measured using immunohistochemistry. The ER expression levels of the two groups were compared, and the relationship between the expression of ERs and serum UA levels was analyzed. Mean serum UA levels in the LN group were significantly higher than those of the IgA nephropathy group, while the mean creatinine levels and GFRs of the two groups were similar. Pathological changes in the LN group were significantly more severe than those in the IgAN group. ERβ was expressed in renal tubular epithelial cells in both groups, but not in the glomeruli. ERβ expression in the LN group was significantly lower than that in the IgAN group. ERβ expression scores significantly negatively correlated with serum UA levels. These findings suggest that the expression of ERβ in premenopausal female SLE patients may cause hyperuricemia, and may subsequently promote glomerular damage, suggesting that ERβ may be involved in UA excretion.